Long‐Term Outcome of Consecutive Patients With Previous Coronary Bypass Surgery, Treated With Newer‐Generation Drug‐Eluting Stents - Liefke C. van der Heijden; Marlies M. Kok; Paolo Zocca; Hanim Sen; Marije M. Löwik; Silvia Mariani; Frits H. A. F. de Man; Marc Hartmann; Martin G. Stoel; K. Gert van Houwelingen; J. (Hans) W. Louwerenburg; Gerard C. M. Linssen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundPercutaneous coronary intervention (PCI) in patients with previous coronary artery bypass grafting (CABG) is associated with adverse clinical events. Although newer generation drug‐eluting stents showed favorable short‐term safety profiles, there is a lack of long‐term outcome data. We evaluated the impact of previous CABG on 5‐year clinical outcomes of patients treated with PCI using newer‐generation drug‐eluting stents. Methods and ResultsIn this patient‐level pooled analysis of the prospective TWENTE (The Real‐World Endeavor Resolute versus Xience V Drug‐Eluting Stent Study in Twente) trial and nonenrolled TWENTE registry, we assessed a consecutive series of patients who underwent PCI with newer‐generation drug‐eluting stents for non–ST‐segment–elevation acute coronary syndromes or stable angina. Of all 1709 patients, 202 (11.8%) had a history of CABG. Patients with previous CABG had significantly higher 5‐year rates of cardiac death (10.4% versus 4.3%; P<0.001) and target vessel revascularization (25.0% versus 8.1%; P<0.001). These differences remained statistically significant after adjustment for differences in baseline characteristics. Landmark analysis revealed that from 1‐ to 5‐year follow‐up, the rates of cardiac death (8.1% versus 3.2%; P<0.001) and target vessel revascularization (17.1% versus 5.9%; P<0.001) were significantly higher in patients with previous CABG. Among patients with a history of CABG, PCI of an obstructed vein graft was associated with a higher rate of 5‐year target vessel revascularization (P=0.003). ConclusionsAt 5‐year follow‐up after PCI with newer‐generation drug‐eluting stents, the risk of cardiac death and target vessel revascularization was significantly higher in patients with previous CABG. The target vessel revascularization rate was highest in patients who underwent PCI of obstructed vein grafts.